Imaging characteristics of BRAF-mutant non-small cell lung cancer by functional class. (March 2019) - Mendoza, Dexter P.; Dagogo-Jack, Ibiayi; Chen, Tianqi; Padole, Atul; Shepard, Jo-Anne O.; Shaw, Alice T.; Digumarthy, Subba Rao
Highlights: CT features of the primary tumor are not different among BRAF mutation classes. Patterns of metastasis may be different among the different BRAF mutation classes. Class I BRAF-mutated NSCLC are more likely to have intrathoracic metastases. Class II and III mutated NSCLC are more likely to have intra-abdominal metastases. Abstract: Objectives: Mutations in the BRAF gene have emerged as a validated molecular target in the treatment of non-small cell lung cancer (NSCLC). These mutations can be classified into three functional classes based on their mechanisms of oncogenesis. The relationship between these functional classes and their imaging features has not been systematically investigated. The goal of this work is to determine if imaging features of the primary tumor and the pattern of metastasis correlate with the functional class of BRAF mutation. Methods: We reviewed pre-treatment computed tomography (CT) images of patients with BRAF-mutated NSCLC with known functional class. We assessed and recorded the features of the primary tumor and the patterns of lymphadenopathy and distant metastasis. Wilcoxon rank-sum test and Kruskal-Wallis test were performed to compare continuous characteristics, and Fisher's exact test was used to compare categorical features between groups. Results and Conclusions: 105 patients with BRAF-mutant NSCLC had pre-treatment imaging available for review (n = 43 class I, n = 40 class II, and n = 22 class III). Approximately half of the primary tumors were considered masses (n = 54/105, 51%) and most were solid (n = 81/105, 77%). There were no statistically significant differences in imaging features of the primary tumor among the three functional classes. Intrathoracic metastases occurred more frequently in class I tumors compared to tumors with class II and III mutations (p = 0.03). The odds of class I mutation were higher among tumors involving the pleural space (OR: 4.39, 95% CI: 1.11–17.4) and lower among tumors disseminating to the abdomen (OR: 0.25, 95% CI: 0.07-0.92). Our findings suggest that class I (V600) mutated NSCLC may be more likely to have intrathoracic metastases, while classes II and III (non-V600) mutated NSCLC may be more likely to have intra-abdominal metastases at the time of presentation.